PENGARUH PENEMPATAN TENAGA KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. KENCANA AMAL TANI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Kusmana, Kusmana (Eko dan Bisnis: Riau Economic and Business Review, 2018)
The research was conducted at PT. Kencana Amal Tani District of Seberida Indragiri Hulu. The purpose of this study was to determine the effect of employment and compensation simultaneously on job satisfaction of employees at PT. Kencana Amal Tani District of Seberida Indragiri Hulu, to determine the effect of partial employment on job satisfaction of employees at PT. Kencana Amal Tani District of Seberida Indragiri Hulu, and to determine the effect of the partial compensation of the job satisfaction of employees at PT. Kencana Amal Tani District of Seberida Indragiri Hulu. The population in this study were all employees of PT. Kencana Amal Tani District of Seberida Indragiri Hulu in 2014 amounted to 83 people. Respect for a population of only 83 people, the authors took a sample of 83 people. Therefore, this study is called a population study or research census. The method used to analyze the data is to use quantitative methods with multiple linear regression, t test and F test. Based on the results of research and discussion, it can take several conclusions as follows: Employment and compensation simultaneously significant effect on job satisfaction at. Kencana Amal Tani District of Seberida Indragiri Hulu. This can be seen by the F test results obtained F count > Ftable is 3387.323 > 3.11. This means that Ho is rejected and Ha accepted, meaning the simultaneous employment and compensation effect on job satisfaction; Employment partially influence on job satisfaction at. Kencana Amal Tani District of Seberida Indragiri Hulu. It is derived from the multiple regression calculation results obtained tcount > ttable ie 50.348 > 1.987608; Partially compensated no effect on job satisfaction at. Kencana Amal Tani District of Seberida Indragiri Hulu. It is derived from the multiple regression calculation results obtained tcount < ttable is -18.851 < 1.987608